Commercial baby foods available in the Portuguese marketplace and the application of Nutrient Profile Models – the compliance assessment - Santos, Mariana (2021)
Background: Scientific evidence suggests that nutritional and metabolic exposure during critical periods of early human development (“the ﬁrst 1000 days”) may have a long-term effect on health in adulthood. An investment in nutrition at the earliest possible stage, providing appropriate complementary feeding, is critical to ensuring growth and development and to prevent noncommunicable diseases (NCDs). Food and drinks high in fats, free sugars and salt are being marketed for consumption by young children and represent a particular concern. Aim: This study aims to determine the compliance of complementary foods (CACF) for infants and young children sold in the Portuguese marketplace according to the WHO draft Nutrient Profile model (NPM) for infants and young children between 6 and 36 months (1). Methods: A sample of 128 complementary foods (CACFs) for infants and young children was collected. Using nutritional food label information, a database was created. The products were divided into four food categories: dry, powdered and instant cereals, dry finger foods and snacks, meals with chunky pieces and soft–wet spoonable, ready-to-eat foods. Packaging information was used to determine sodium, fat and sugar content per 100 g product and percentage energy from total sugar by food category. Results: Twenty-eight products (22%) comply with all the criteria established in the NPM. All the evaluated dry, powdered and instant cereals, dry finger foods and snacks and meals with chunky pieces (n =55) comply with the recommendations proposed for total fat (≤4.5 g/100 kcal). Analysis of the energy contribution from total sugars reveals that 9 % (n=5) of dry finger foods and snacks comply with the proposed criteria of < 15% total energy from total sugars. For the 73 soft–wet spoonable, ready-to-eat foods assessed, 74 % (n=54) comply with the sodium thresholds of 50 mg/100 kcal, 64 % (n=47) had a content ≥ 60 Kcal/100 g product and 74 % (n=54) contained over 20% of energy derived from sugar. Conclusions: The commercial baby foods available in the Portuguese marketplace are characterised by products with high proportion of calories derived from sugar, promoting an environment that encourages development of sweet-taste preferences and adverse health outcomes resultant from the overconsumption of sugar in early life. This study provide policy-makers with data to design evidence-based nutrition policies supporting food product reformulation, to provide healthier options and preventing and controlling NCDs. Main Messages: There is an urgent need for updated regulations to support and guide product reformulation. A nutrient profile model for CACFs will establishes compositional thresholds and provides guidance on product-labelling and promotion